Addressing 5G enhanced mobile broadband and lean signaling based on dual-connectivity and channel hardening occurence - Monteiro, Victor Farias (2018)
Fifth Generation (5G) systems are expected to deploy massive Multiple Input Multiple Output (MIMO) antennas and operate with millimeter waves in order to support a significantly increasing data traffic. With more antennas and wider bandwidth, Channel Quality Indicator (CQI) estimation and reporting will be computationally demanding, increasing signaling between Base Stations (BSs) and User Equipments (UEs). In this context, the present thesis analyzes two strategies to address both problems: increasing data traffic and signaling. The first strategy is to exploit the reduction of channel fluctuations due to the use of narrow beams with large antenna arrays, i.e., the channel “hardens”. When this phenomenon happens, upper layer functions related to measurements can be optimized and signaling reduced. The second strategy concerns the adoption of a tight integration between 5G NR and LTE. More precisely, the UEs would be allowed to be simultaneously connected to both Radio Access Technologies (RATs), the so-called Dual Connectivity (DC). Before addressing these two strategies, we present an overview of the main 5G features used in this thesis and standardized in 3rd Generation Partnership Project (3GPP) specification release 15. After that, we present general analyses related to DC and Channel Hardening (CH) occurrence. Finally, we investigate these concepts from the perspective of Radio Resource Allocation (RRA). More specifically, frameworks related to CQI measurement and reporting based on CH occurrence are proposed. Besides, we also propose procedures for base station selection and resource assignment in a multi-RAT multi-connectivity system. Numerical analyses considering 5G system parameters are presented validating the proposed methods and showing that they improve system performance.